2015
DOI: 10.1111/jam.12908
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation performance of lactic acid bacteria in different lupin substrates-influence and degradation ability of antinutritives and secondary plant metabolites

Abstract: This work contributes to the fundamental knowledge of the metabolism of lactic acid bacteria during fermentation of lupin substrates. Fermentation of lupin raw materials could be used to improve the nutritional value of the substrates due to the reduction of antinutritives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 50 publications
3
30
0
1
Order By: Relevance
“…Fermentation using bacteria (Fritsch et al, 2015) or yeast (Kasprowicz-Potocka et al, 2015) caused also the decrease in phytate content by about 20%, and it was confirmed in our study. The observed changes indicate that fermentation increases the activity of native phytase, which can disintegrate insoluble organic complexes with minerals.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Fermentation using bacteria (Fritsch et al, 2015) or yeast (Kasprowicz-Potocka et al, 2015) caused also the decrease in phytate content by about 20%, and it was confirmed in our study. The observed changes indicate that fermentation increases the activity of native phytase, which can disintegrate insoluble organic complexes with minerals.…”
Section: Discussionsupporting
confidence: 74%
“…Vidal-Valverde et al (1993) by fermenting lentils received a total reduction of these compounds. Also, lupine fermentation conducted by Fritsch et al (2015) using Bifidobacterium lactis significantly reduced the RFO content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lactobacillus acidophilus strain recorded the highest reduction of antinutrition factors and simmondsin content followed by L. plantrium , Bifidobacterium angulatum , and Streptococcus thermophiles . The results agreed with Swezey et al (), Van Boven et al (), Labib et al (), El‐Adawy et al (), Aljuobori et al (), and Fritsch, Vogel, and Toelstede () who reported that some LAB such as L. acidophilus , L. plantrum , and L. arizonensis could remove simmondsin and antinutrition factors (phenols and phytic acid) by LAB production of phytase that is responsible for degradation of phytic acid and plant secondary metabolites. The results corroborate reports that DJM could be a good source of protein and other nutrients (Kumar et al, ).…”
Section: Resultssupporting
confidence: 89%